"DIURNAL APPEARANCE MOVEMENTS OF LUMINAIRES. METHODOLOGY OF TEACHING THE SUBJECT "CONSTELLATIONS" - R.X.Ibragimova; M. A. Raximberdiyeva; N. A. Tojiyeva (Galaxy International Interdisciplinary Research Journal, 2022)
This article provides recommendations on the milk movements of lamps and the methodology of teaching the subject of star categories.